Effectiveness Of Utilizing Educational And Information Media To Improve Knowledge And Attitude In Prevention Of Infectious Diseases In Passengers At The Pulogebang Integrated Terminal Indonesia - Nuraini, Novia; Aziz, Abdul; Rosidawati, Rosidawati; Lihanda, Arya Duta; Aufa, Achmad Ikramul; Risqullah, Rakha Rasika (International Journal of Health Sciences, 2025)
Infectious diseases are a public health problem that can spread very quickly, especially in public places with high mobility and social interaction. The study aims to determine the effectiveness of the use of educational and information media in terminals as an effort to prevent infectious diseases. The quasi-experimental research method without a control group to determine the effectiveness of animated videos and booklets as a means of educating passengers on the prevention of infectious diseases at the Pulogebang integrated terminal. The research sample was 80 passengers, the first group was given animated videos, and the second group was given booklets with the same material. Observations were made at that time and the results of the study showed an increase in knowledge in the Animated Video group by 1.02 and in the Booklet group by 1.44. There was an increase in attitudes in the Animated Video group by 2.40 and in the Booklet group by 1.26. The results of the analysis showed a significant difference in attitudes before and after the intervention with a p value of 0.000 (<0.05). Conclusion, animated video media is more effective in increasing passenger understanding and attitudes towards the prevention of infectious diseases than booklet media.